Changes in exclusive breastfeeding practices and its determinants in India, 1992–2006: analysis of national survey data. Issue 1 (December 2015) - Chandhiok, Nomita; Singh, Kh.; Sahu, Damodar; Singh, Lucky; Pandey, Arvind
Abstract Background Exclusive breastfeeding up to six months is considered to be beneficial for the health and wellbeing of infants and mothers. To guide policy makers in the development of targeted breastfeeding promotion strategies, changes in the effect of predictor variables on exclusive breastfeeding practices in India were examined. Methods Data from two rounds of the National Family Health Survey (NFHS) carried out in India during 1992–93 (NFHS-1), and 2005–06 (NFHS-3) were analysed. A total of 34, 176 and 25, 459 births under three years of age in NFHS-1 and NFHS-3 respectively comprised the sample. Exclusive breastfeeding was defined as infants zero to five months of age who received only breast milk in previous 24 h. The practice of exclusive breastfeeding was examined at different ages (1, 4 and 6 months) against a set of predictor variables using bivariate and multinomial logistic regression in conjunction with the multiple classification analysis. Results Overall 46.3 per cent and 48.6 per cent of infants under six months of age were exclusively breastfed in NFHS-1 and NFHS-3 respectively. The proportion declined with each additional month of age, and at four months only 24 per cent infants in NFHS-1 and 31 per cent infants in NFHS-3 were exclusively breastfeeding. In the NFHS-1 a higher proportion of infants perceived to be small size at birth and those with mothers in gainful employment were exclusively breastfed. While in infants of mothers living in urban areas, older mothers (aged ≥ 35 years), more literate mothers, belonging to a higher standard of living index, preceding birth interval less than two years, and in those who had antenatal/natal care, a lower proportion of exclusive breastfeeding was observed at different ages of the infant. However, in the NFHS-3, children of older mothers and of those who were less educated the proportion of exclusive breastfeeding was significantly greater at one month of age. In the age segment one to four months; exclusive breastfeeding was significantly lower in infants born to older mothers, from medium standard of living households and perceived to be of small size at birth. Infants of mothers who were more educated, aged ≥ 35 years, living in urban areas and who had antenatal/natal care were the factors associated with a lower proportion of exclusive breastfeeding at six months of age. Conclusions The rate of exclusive breastfeeding in India continues to be sub-optimal with no appreciable gains in the last ten to fifteen years. Interventions that seek to increase exclusive breastfeeding should be timely with an increased focus on mothers with infants four to six months of age and in those who are most at risk of early discontinuation of exclusive breastfeeding.